2021
DOI: 10.3389/fbioe.2021.730663
|View full text |Cite
|
Sign up to set email alerts
|

Designing Modular Cell-free Systems for Tunable Biotransformation of l-phenylalanine to Aromatic Compounds

Abstract: Cell-free systems have been used to synthesize chemicals by reconstitution of in vitro expressed enzymes. However, coexpression of multiple enzymes to reconstitute long enzymatic pathways is often problematic due to resource limitation/competition (e.g., energy) in the one-pot cell-free reactions. To address this limitation, here we aim to design a modular, cell-free platform to construct long biosynthetic pathways for tunable synthesis of value-added aromatic compounds, using (S)-1-phenyl-1,2-ethanediol ((S)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 51 publications
(76 reference statements)
1
17
0
Order By: Relevance
“…Further increase of CFPS reaction time did not significantly improve the product yield, perhaps as a result of other limiting factors in the reaction. This result is similar to a previous report that 2-h CFPS reaction was the best for enzyme expression before mixing and the resultant bioconversion [ 30 ].
Fig.
…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Further increase of CFPS reaction time did not significantly improve the product yield, perhaps as a result of other limiting factors in the reaction. This result is similar to a previous report that 2-h CFPS reaction was the best for enzyme expression before mixing and the resultant bioconversion [ 30 ].
Fig.
…”
Section: Resultssupporting
confidence: 92%
“…For example, the reaction format and cofactor supplementation can be readily manipulated to achieve high productivity. Previous studies also have demonstrated the flexibility of cell-free systems by designing modular CFPS reactions, expressing enzymes in separate modules, and eventually mixing cell-free modules for long metabolic pathway construction and product formation [ 30 , 47 ]. Third, cell-free systems without the use of living cells are tolerant to toxic compounds such as the cellular toxic NO if it is highly accumulated in cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell-free platforms also have numerous advantages over cell-based platforms on an industrial scale, such as faster development times, adaptability to various production schemes, resistance to conditions toxic to cell-based systems, and cost-effectiveness at scale [25]. The increasing demand for low-cost and sustainable products manufactured from low-carbon emission methods can also be addressed using cell-free systems optimized to utilize more sustainable carbon utilization pathways and green energy regeneration modules [20,25,26]. While cell-free platforms have been demonstrated to be adaptable to industrial production schemes, they can also be utilized for smaller-scale on-demand production of target molecules.…”
Section: Introductionmentioning
confidence: 99%
“…While cell-free platforms have been demonstrated to be adaptable to industrial production schemes, they can also be utilized for smaller-scale on-demand production of target molecules. This is particularly useful for the on-demand production of therapeutics, of which many niche drugs do not have the demand for pharmaceutical companies to warrant building expensive cell-based infrastructure to produce them [26]. Cell-free systems could be used at a scale where the on-demand manufacturing of custom therapeutics for individual customers would be feasible [27].…”
Section: Introductionmentioning
confidence: 99%